PERANCANGAN DAN PEMBUATAN SISTEM INFORMASI PPDB (PENERIMAAN PESERTA DIDIK BARU) ONLINE BERBASIS WEB PADA SMA MUHAMMADIYAH 4 KENDAL - adminjfik adminjfik; Yusuf Wahyu Setiya Putra Mila; Ahmad Fakhrudin Mila (Fakultas Komputer Dan Desain, 2022)
New Student Admission (PPDB) SMA Muhammadiyah 4 Kendal Currently still using the manual method, namely filling out registration forms and completing the requirements directly to school. This makes it difficult for officers to manage data on prospective new students. In addition, when announcing the PPDB results, SMA Muhammadiyah 4 Kendal is currently still using the manual method, namely by pasting the Announcement Results on the bulletin board. Of course this is less effective, because students have to come to school to see the results of the announcement. To be able to overcome the problems described above, a web-based online PPDB (New Student Admission) Information System was designed at SMA Muhammadiyah 4 Kendal.This type of research is qualitative research. The software development method uses the Waterfall Model. Software testing is done through black-box testing. The purpose of this system is to make it easier for prospective students to register, view announcement results, do re-registration. The results of this study are the Web-Based Online PPDB Information System at SMA Muhammadiyah 4 Kendal was successfully created using the PHP Programming Language and MySQL database, it can assist the school in carrying out new student admissions activities, and for prospective students it can make it easier to carry out the registration process, see Announcement results and re-register